The effects of vitamin E and selenium on cypermethrin-induced oxidative stress in rats ahmet - Ateşşahin, Ahmet; Yilmaz, Seval; Karahan, Izzet; Pirinçci, Ibrahim; Taşdemir, Bülent (My University, 2005)
The aim of this study was to investigate whether vitamin E (VitE) and selenium (Se) or VitE plus Se have any the protective and/or augmented effects on cypermethrin (CYP)-induced oxidative stress in liver, brain, kidney and blood in rats. Rats were treated orally with daily 50 mg/kg (? 1/4 ED50) of CYP in corn oil for five days after administrations of VitE (100 mg/kg sc.), Se (0.1 mg/kg, sc.) and VitE plus Se for three days. Malondialdehyde (MDA) concentrations, glutathione peroxidase (GSH-Px) and catalase (CAT) activities were measured in tissues and blood samples. MDA concentrations in all tissues except plasma, and GSH-Px activities in liver and erythrocytes were significantly increased, but CAT activities in all tissues except erythrocytes were decreased in CYP treated group when compared with the control group. Treatment with VitE prior to CYP reduced sensitivity on CYP-induced oxidative stress. The use of Se was observed to increase both MDA concentrations and antioxidant systems such as GSH-Px and CAT activities. On the other hand, VitE plus Se caused complex alterations in the antioxidant system on the oxidative stress induced by CYP. The results suggest that CYP can induce oxidative stress and VitE can modify CYP metabolism and play a protective role against CYP-induced oxidative stress. © TÜBİTAK.
Keywords: Catalase; Cypermethrin; Glutathione peroxidase; Lipid peroxidation; Oxidative stress; Selenium; Vitamin E